Democratic Republic of Sao Tome and Principe : Third and Fourth Reviews under the Extended Credit Facility Arrangement, Extension of the Arrangement, and Modification of Performance Criteria-Press Release; Staff Report; and Statement by the Executive Director for the Democratic Republic of Sao Tome and Principe. (IMF Staff Country Reports; Country Report ;, 2017)
This paper discusses Sao Tome and Principe's Third and Fourth Reviews Under the Extended Credit Facility Arrangement, Extension of the Arrangement, And Modification of Performance Criteria (PCs). Program implementation is broadly back on track. After missing the end-2016 fiscal targets by large margins, the government adopted corrective measures and met all five end-June 2017 PCs. The implementation of structural reforms under the program is progressing, albeit at a much slower pace than anticipated due mainly to capacity constraints and delays in the delivery of technical assistance. The IMF staff recommends the completion of the joint third and fourth reviews, approval of the extension to end-2018, and rephasing of the program.